O Lazer e as relações socioambientais em Belém - Pará - BAHIA, Mirleide Chaar (Universidade Federal do Pará, 2012)
This thesis developed an analysis of the dynamics of the relational field of leisure in urban public green areas. The main objective was to analyze the experiences of leisure and the intermediation in socio-environmental relations in Belém, based on the mapping of the relatio ns between elements in the leisure area, the configuration of the relational field, through the experiences of these three areas, which are the Rodrigues Alves Park, Amazon Zoo botanic Garden, Batista Campos Square and the State Park of Utinga, and programs, projects and activities for leisure and the environment existing in them. As a theoretical and methodological option, the guidelines proposed by Pierre Bourdieu were followed, exploring the theoretical and methodological investigations and the concepts of field and habitus, but is also grounded on theories that deal with recreation, urbanization of Belém, in accordance with the nature and urban public green areas. Based on a qualitative nature, this research considered exploratory studies, through the combination of literature review, document analysis and field research, interviews with simple observation and non-directive interviews. It was observed that there is recognition of the existence of institutionalized leisure, since in modern society, space and time in large cities acquires such character, but is also evident that the occupant experiences leisure as free practice, such as human need, many times uses this as an intermediary in their relations with nature. In this sense, it was realized that there are various forms of relationships in these areas and a quality leisure could improve such relationships. However, in the relational field of leisure in urban public green areas, some representatives of public institutions that should be present in these areas and act directly in that field, appear to be absent.